Regulatory challenges in integrating hijāmaћ professional development into Malaysia's healthcare system - Asar, A. K.; Aziman, Abdullah (Universiti Malaysia Pahang, 2023)
This study delves into the intricate challenges of integrating hijāmaћ professional development into Malaysia's healthcare system. Despite its significance, incorporating hijāmaћ into the national healthcare framework faces significant hurdles, with regulatory challenges taking center stage. The research thoroughly examines the Traditional and Complementary Medicine Blueprint 2018-2027 for Health Care (TCMBP) established by the Ministry of Health, Malaysia, revealing a spectrum of regulatory challenges as major obstacles. The paper proceeds to propose potential solutions, targeting policymakers responsible for navigating these regulatory barriers. The insights drawn from this study contribute significantly to ongoing discussions about harmoniously merging hijāmaћ professional development into contemporary healthcare systems. It provides a nuanced perspective that balances the preservation of this cultural therapy with the assimilation of modern medical advancements. This sets the stage for a more comprehensive and inclusive healthcare approach that resonates effectively with Malaysia's diverse population. This synergy between traditional and modern medical practices not only respects cultural heritage but also has the potential to transform healthcare outcomes, promoting sustainability and enhancing societal well-being. It emphasizes the importance of recognizing traditional practices within modern healthcare, offering a path to improved healthcare services for Malaysia's diverse society.